2015
DOI: 10.1093/brain/awv219
|View full text |Cite
|
Sign up to set email alerts
|

Loss of phosphodiesterase 10A expression is associated with progression and severity in Parkinson’s disease

Abstract: The mechanisms underlying neurodegeneration and loss of dopaminergic signalling in Parkinson's disease are still only partially understood. Phosphodiesterase 10A (PDE10A) is a basal ganglia expressed dual substrate enzyme, which regulates cAMP and cGMP signalling cascades, thus having a key role in the regulation of dopaminergic signalling in striatal pathways, and in promoting neuronal survival. This study aimed to assess in vivo the availability of PDE10A in patients with Parkinson's disease using positron e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 52 publications
2
113
1
Order By: Relevance
“…Similarly, neither previous studies of patients with schizophrenia (RN Gunn, personal communication) 16 or Parkinson's disease, nor experimental animal models have established a correlation between age and PDE10A availability. 13,35 Another limitation was the difference in coffee and smoking habits between the two The difference between groups was significant at Po0.001 as revealed with a Mann-Whitney U-test (Levene's test revealed no significant difference in variance, Fo 1).…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, neither previous studies of patients with schizophrenia (RN Gunn, personal communication) 16 or Parkinson's disease, nor experimental animal models have established a correlation between age and PDE10A availability. 13,35 Another limitation was the difference in coffee and smoking habits between the two The difference between groups was significant at Po0.001 as revealed with a Mann-Whitney U-test (Levene's test revealed no significant difference in variance, Fo 1).…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…[8][9][10][11][12] Moreover, patients with other striatal disorders, such as Parkinson's and Huntington's disease, have lower availability of striatal PDE10A early in the disease course. 13,14 Although PDE10A inhibition has shown promise as a novel target of the treatment of schizophrenia, 15 recently the first positron emission tomography (PET) study of PDE10A expression in patients with schizophrenia found no difference compared to healthy controls using the [ 11 C]IMA107 ligand. 16 However, the sample size was small and did not include treatment-resistant patients treated with diazepines such as clozapine.…”
Section: Introductionmentioning
confidence: 99%
“…Among PDEs family, PDE10A is expressed almost exclusively in the striatum (Coskran et al, 2006;Lakics, Karran, & Boess, 2010), where it modulates cAMP/PKA/DARPP-32 signaling cascade thus having a key role in the regulation of striatal output and in promoting neuronal survival (Girault, 2012;Nishi et al, 2008). Using [ 11 C]IMA107 PET, our group has recently investigated PDE10A expression in 24 levodopa-treated moderate to advanced PD patients (Niccolini, Foltynie, et al, 2015;Niccolini, Haider, et al, 2015). PD patients showed lower [ 11 C]IMA107 binding in the caudate, putamen, and pallidum compared to healthy controls.…”
Section: Phosphodiesterasesmentioning
confidence: 99%
“…PD patients showed lower [ 11 C]IMA107 binding in the caudate, putamen, and pallidum compared to healthy controls. Longer PD duration and higher UPDRS-III motor scores correlated with lower [ 11 C]IMA107 binding in the caudate, putamen, and pallidum (Niccolini, Foltynie, et al, 2015;Niccolini, Haider, et al, 2015). Higher Unified Dyskinesia Rating Scale (UDysRS) scores in those PD patients with levodopa-induced dyskinesias correlated with lower [ 11 C]IMA107 binding in the caudate and putamen.…”
Section: Phosphodiesterasesmentioning
confidence: 99%
See 1 more Smart Citation